ANALISIS KETERAMPILAN KOLABORASI SISWA SMA DALAM PEMBELAJARAN FISIKA MELALUI PENDEKATAN STEM - Muhamad Nur Dandy, - (2021)
This study was conducted to analyze collaboration skills through a STEM approach. The analysis of collaboration skills in this study is viewed from three aspects, namely aspects of participation, perspective taking, and social regulation. Students work in groups of three to four people in each group. Students work together to solve problems about optical instrument material. The method used in this research is descriptive explorative method. Data were taken from 8 groups which were grouped randomly from 32 students in one of the senior high schools in Bandung. Data in the form of student conversations are classified according to the indicators of Collaborative Problem Solving skills based on keywords, then categorized based on four levels, namely beginner (level 1), emerging (level 2), intermediate (level 3), and advanced (level 4). The results of this study indicate that students are at various levels with different analysis results. The assessment used in this study can be used as a database and instrument for measuring student collaboration skills. Keywords: collaboration skills, student collaboration analysis, STEM approach